Potential therapeutic effect of turmeric (Curcuma longa) against adverse effects of penconazole fungicide to white rats - Abdel Rasoul, Mona; Marei, Gehan (International Journal of Pharmacology and Toxicology, 2016)
This study aimed to investigate the prophylactic effect of turmeric (Curcuma longa) Rhizome Ethanolic extract (CLRE) at 250 mg/kg as antioxidant effects against penconazole induced sub-acute toxicity. Hepatic, renal and testicular pathological changes caused by oxidative damage induced by penconazole in rats were biochemically and histologically evaluated. Male rats were treated with penconazole, via oral route, at doses of 0.5 mg/ kg body weight (b.w.; acute reference dose, ARfD), 25 mg/kg b.w. (no observed adverse effects level, NOAEL) and 100 mg/ kg b.w. (1/20 lethal dose [LD50]) for 28 consecutive days. Penconazole treatments had significant (p < 0.05) and gradual reductions in body and relative testicular weight accompanied by significant elevation in the relative liver and kidney weights. Significant increase serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dhydrogenase(LDH), gamma-glutamyl transferase (GGT), creatinine (Cre), uric acid and blood glucose was observed due to penconazole treatments. However, total protein and testosterone hormone were significantly decreased. Exposure to penconazole caused increase in lipid peroxidation (LPO) and decreased of liver and kidney antioxidant enzymes activity as catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx). Histopathological studies confirmed the ameliorative beneficial effects of turmeric biochemical parameters. On the basis of this study, the use of tumeric rhizomes as a functional food or as a nutraceutical product could be a useful approach to protect individuals who are regularly exposed to penconazole.